Patient-centered infertility care from an Arab perspective: A review study - Hana Hasan Webair; Tengku Alina Tengku Ismail; Shaiful Bahari Ismail (Middle East Fertility Society Journal, 2018)
Background: Patient-centeredness was listed as the sixth quality element by the Institute of Medicine in 2001. Cultural differences should be acknowledged when defining patient-centeredness. Although there are numerous sources of literature that studied patient-centered infertility care, few include members of the Arab population. Objectives: This review aims to answer two questions: What do Arab patients prefer, value, and expect from infertility medical care? How was patient-centered infertility care studied in Arab patients? Search strategy: A systematic search was conducted on seven electronic databases published up until March 2017. Selection criteria: Studies evaluated the infertile patients' preferences and expectations concerning infertility care. Participants were Arab patients who sought care for infertility. The outcome was patient-centered infertility care. Data collection and analysis: The reviewers carried out data extraction of specific outcomes and evaluated each study using the Mixed Methods Appraisal Tool. Main results: A total of 629 citations were identified. However, only 6 were eligible for analysis. All studies were monocentric. All but one of them were quantitative. The patient-centered care outcome measures in most of the studies were respect for patients’ preferences and/or physical comfort concerning a specified diagnostic or therapeutic intervention. Only one study explored patients’ experiences and found that emotional support, information, communication, education, and coordination and integration of care were appreciated dimensions. Conclusions: We found that no study comprehensively described what infertile Arab couples prefer, need, and value. A contributing factor to this conclusion may be in the methodologies used. Further studies are needed to adequately answer the research questions.